The Effects of Design Parameters on The UNICORE Type Transformer Inrush Current - Karaarslan, Mehlika Şengül; Alboyacı, Bora; Çınar, Mehmet Aytaç; Tekdemir, İbrahim Gürsu (Kocaeli Üniversitesi, 2022)
In this study, it is aimed to fill the information gap about the effects of designed parameters in UNICORE type transformers inrush current. Considered prameters are the flux density, the core construction and the lamination thickness of the transformers. In this context, the UNICORE transformer was compared with the conventional wound core (CWC) transformer by using three-dimensional finite-element configuration. In order to get real system response, the study was carried out experimentally. Analyzing the test results, the effects of the core material and design parameters on the magnitude, duration and harmonic content of inrush current on these types of transformers were detected. Tests were performed by using a programmable power source and analyzed data sets were recorded by scopemeter.
Keywords: Electrical Engineering; Elektrik Mühendisliği